Determinan Struktur Modal dan Dampaknya terhadap Nilai Perusahaan (Studi pada Perusahaan Makanan dan Minuman di Bursa Efek Indonesia) - Sari, Dessy Handa; Djazuli, Atim; Aisjah, Siti (Universitas Brawijaya, Indonesia, 2013)
The study aimed at measuring and analyzing the effects of probability, firm size, growth, assetstructure and non debt tax shield to the capital structure and the impact to the firm value of food andbeverage companies in the Indonesian Stock Exchange. It is expected the results of the research able to givecontribution for study development about financial management, especially at the capital structure andfirm value. Study population is the food and beverage companies that is listed in the Indonesian StockExchange 2005-2011, in data collection, the census method was used. The regression of two stage methodwas used to analyze the qualitative data. The study results are to find the influence between profitability,firm size and capital structure, but did not find influence between able growth, asset structure and non debttax shield to capital structure, and the influence capital structure and firm value.